Evaluate The Effect of Immediate Finishing and Polishing of Composite Resin on its Color Stability - عبد الله, عزيز (Latakia University Journal -Medical Sciences Series, 2024)
Aim: the aim of this study was to evaluate the effect of immediate finishing and polishing of the tetric N ceram composite resin on its color stability. Materials and Methods: The research sample included 40 blocks of tetric N ceram composite, which were divided into two groups according to the time in which the finishing and polishing procedures were carried out. The first group was finished immediately after curing, and the second group was finished after 24 hours. After that, the samples were immersed in the coffee solution and then placed in the incubator for a 48 hours at 37°C and 100% humidity. After removing them from the incubator, the samples were washed for a minute with saline, then dried with tissues, and the color was recorded using Easz shade device. The L, a, and b values ​​were recorded after staining, and the appropriate statistical tests were conducted. Results: There was no statistically significant difference in the coloration of the composite whether it was finished and polished immediately after curing or after 24 hours. Conclusion: Within the limitations of this study, it can be concluded that Tetric N ceram restorations can be finished immediately because immediate finishing does not affect their coloration.